Regulation of Staphylococcus aureus Type 5 and Type 8 Capsular Polysaccharides by CO(2) - Herbert, Silvia (American Society for Microbiology, 2001)
Staphylococcus aureus expression of capsular polysaccharide type 5 (CP5) has been shown to be downregulated by CO(2). Here we show that CO(2) reduces CP5 expression at the transcriptional level and that CO(2) regulates CP8 expression depending on the genetic background of the strains. Growth in the presence of air supplemented with 5% CO(2) caused a significant decrease in CP8 expression in four S. aureus strains, a marginal effect in four strains, and higher CP8 expression in strain Becker. Absolute CP8 expression in the nine S. aureus strains differed largely from strain to strain. Four groups of strains were established due to sequence variations in the promoter region of cap5 and cap8. To test whether these sequence variations are responsible for the different responses to CO(2), promoter regions from selected strains were fused to the reporter gene xylE in pLC4, and the plasmids were electrotransformed into strains Becker and Newman. XylE activity was negatively regulated by CO(2) in all derivatives of strain Newman and was always positively regulated by CO(2) in all derivatives of strain Becker. Differences in promoter sequences did not influence the pattern of CP8 expression. Therefore, the genetic background of the strains rather than differences in the promoter sequence determines the CO(2) response. trans-acting regulatory molecules may be differentially expressed in strain Becker versus strain Newman. The strain dependency of the CP8 expression established in vitro was also seen in lung tissue sections of patients with cystic fibrosis infected with CP8-positive S. aureus strains.